Pengaruh Motivasi Kerja Dan Kompetensi Terhadap Kinerja Pegawai Pada Kantor Badan Pengelolaan Keuangan Dan Pendapatan Daerah ( BPKPD ) Kabupaten Tana Toraja - Welni Toding Allo; Althon K. Pongtuluran; Chrismesi Pagiu (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This study aims to determine the influence of motivation and competence on employees at the Badan Pengelolaan Keuangan Dan Pendapatan Daerah ( BPKPD ) of Tana Toraja Regency. The research method used in this study was quantitative descriptive research with a sample of 72 people. The data analysis technique used in this study is a multiple linear regression test with statistical calculation tools using SPSS version 25.0.The results of this study obtained the equation Y = 18.514 + 0.616 X1 + 0.305 X2 +e. Motivation affects the performance of employees. Competency affects the performance of employees. Motivation and competence a effect on the performance of employees at the Office of the Badan Pengelolaan Keuangan Dan Pendapatan Daerah ( BPKPD ) of Tana Toraja Regency.